Marshall stability properties of asphalt mixture incorporating black rice husk ash - Putra Jaya, Ramadhansyah; Noram Irwan, Ramli; Mohd Rosli, Hainin; Norhidayah, Abdul Hassan; Haryati, Yaacob; Mohd Khairul Idham, Mohd Satar; Muhammad Naqiuddin, Mohd Warid; Azman, Mohamed; Mohd Ezree, Abdullah (Elsevier Ltd, 2018)
The commercial value of black rice husk ash (BRHA) has increased, and it is suitable for use in highway construction. In this study, BRHA waste was ground using a grinding ball mill to fine particles size less than 75μm. Four BRHA contents were considered in the study i.e. 0%, 2%, 4%, and 6% by weight of binder. The asphalt mixture performance of the BRHA was evaluated through Marshall Stability, stiffness, flow, and density test. Test results showed that BRHA can be satisfactorily used as a filler material in order to increases the properties of hot-mix asphalt. Test results also indicate that asphaltic concrete containing 6% BRHA showed excellent performance to Marshall Stability properties.